From Bear Stearns to Anglo Irish : How Eurozone Sovereign Spreads Related to Financial Sector Vulnerability - Mody, Ashoka (IMF Working Papers; Working Paper, 2009)
This paper attempts to explain the recent rise and differentiation of sovereign spreads across the countries of the eurozone. Following the onset of the subprime crisis in July 2007, spreads rose but mainly on account of common global factors. The rescue of Bear Stearns in March 2008 marked a turning point. Countries thereafter were increasingly differentiated. Sovereign spreads of a eurozone country tended to rise when the prospects of its domestic financial sector worsened. It appears, therefore, that the rescue of Bear Stearns created a link between financial sector vulnerabilities and a larger contingent liability on public finances. Following the failure of Lehman Brothers, spreads also rose faster for countries with higher ratios of public debt-to-GDP. These transitional dynamics appear to have concluded with the nationalization of Anglo Irish: sovereign spreads throughout the eurozone jumped, with the jump emphasizing the differentiation by financial sector vulnerability and public debt levels. The results imply that, to varying degrees, countries may have moved to a new regime of weak economic outlook, financial sector fragilities, and strains on public finances.